Asymmetric adjustments in the thai palm oil market - Songsiengchai, Patchaya; Sidique, Shaufique Fahmi; Djama, Marcel; Wan Ngah, Wan Azman Saini (Kasetsart University, 2020)
Drastic movements of global commodity prices and their impact on the Thai palm oil market is a major concern due to Thailand being the third largest producer of crude palm oil (CPO). Although the country is not a net importer, global price changes of the commodity can transmit to domestic markets for palm oil products. This paper analyzed the transmission of Malaysian CPO and world crude oil price changes to the changes in the Thai CPO price using an asymmetric error correction model. The price data used in this paper covers the period from January 1996 to September 2015. The findings showed that the speed of adjustments towards long-run equilibrium were asymmetric and the effects of the world prices on Thai CPO price were significant in both positive and negative deviations. This result calls for policy measures to mitigate the impact of global price movements because CPO is an essential intermediate input in various products and any changes in the Thai CPO price definitely affects the welfare of domestic consumers.